Perbedaan Perkembangan Motorik Halus Anak Prasekolah Antara Yang Mengikuti Paud Dan Tidak Mengikuti Paud Di Desa Kalikotes Kecamatan Kalikotes Klaten - Efendi, Rofi'udin Nur; , Siti Arifah, S.Kp., M.Kes (2016)
Preschool child is a child aged between 3-6 years of age wherein at this time the child is undergoing a process of growth and development is very rapid, thus requiring intensive stimulation of the people around her in order to have a quality of personality in the future. Early childhood education (PAUD) aims to facilitate the growth and development of the whole child, and focus more on the development of all aspects of the child's personality. This study aims to determine differences in fine motor development of preschool children between the follow and not follow PAUD ECD in the village Kalikotes Kalikotes District of Klaten. This research a non-experimental research design descriptive comparative cross-sectional approach. Collecting data using observation sheet DDST, while the data were analyzed using Mann Whitney test. The conclusion of research was the development of fine motor skills of preschool children who follow early childhood everything is normal and Non early childhood largely normal, and there are differences in fine motor skills of children who attend early childhood education with children who do not follow early childhood, where children who attend early childhood have the fine motor skills better than children who do not follow early childhood.